Ketika Idol Menjadi Idola: Dampak Celebrity Worship pada Subjective Well-Being Penggemar Day6 Usia Dewasa Awal - Syntiani Devi; Nita Rohayati; Yulyanti Minarsih (Universitas Darul Ulum, 2025)
The attachment that Day6 fans of early adulthood have to their idol describes behavior that leads to celebrity worship, where the emotional reaction forms an individual's assessment of life satisfaction and positive and negative experiences that are identical to subjective well-being. This study aims to determine the impact of celebrity worship on subjective well-being in early adult of Day6 fans. The method used is quantitative and a convenience sampling technique. The sample selected was Day6 fans aged 20-40 years old, as many as 130 people. The celebrity worship measuring instrument uses the Celebrity Attitude Scale with 22 valid items. While for subjective well-being, the cognitive aspect is measured using the Satisfaction With Life Scale with 5 valid items, and the affective aspect is measured using the Scale of Positive and Negative Experience with 12 valid items. The results of hypothesis testing obtained a significance value of p=0.020 in the entertainment aspect social aspect, p=0.035 on intense personal feeling, and p=0.015 on borderline pathological. These results show that each level of celebrity worship has an impact on the subjective well-being of early adult of Day6 fans.